Multilevel and general linear modeling of weather and time effects on the emotional and behavioral states of children with profound intellectual and multiple disabilities - Herbuela, Von Ralph Dane Marquez; Karita, Tomonori; Toya, Akihiro; Furukawa, Yoshiya; Senba, Shuichiro; Onishi, Eiko; Saeki, Tatsuo (Frontiers in Psychiatry, 2024)
Eliciting the emotional and behavioral states of children with severe or profound intellectual disabilities (IDs) and profound intellectual and multiple disabilities (PIMD) due to their complex and atypical developmental trajectories has become increasingly elusive. Nevertheless, it's evident that the environment, influenced by weather conditions, holds a pivotal role in molding the behaviors, emotions, and interactions of these children. This underscores its significance as a key factor in exploring their communication dynamics. Over a period of five months during the fall and winter, we conducted 105 video-recorded sessions with 20 children aged 8 to 16 who had PIMD/IDs. These sessions aimed to capture the emotional and behavioral states as interpreted by caregivers, while simultaneously collecting indoor and outdoor weather data, location and time data. Using crossclassified multilevel and general linear models adjusted for individual characteristics and location variability with subsequent simple slope analyses, we examined the main and seasonal interaction effects of indoor and outdoor weather indices and time of the day on the emotional and behavioral states. We found that higher atmospheric pressure (atm) and cloudiness levels were associated with increased engagement (atm: p<.05; cloudiness: p<.05), interest (atm: p<.01), and reduced refusal behaviors (atm: p<.01). In contrast, we observed decreased engagement before lunchtime (p<.001) and more refusal or disagreement during inclement or unstable weather conditions, such as lowpressure systems (p<.05) and increasing wind speed (p<.05). During winter, children demonstrated significantly higher levels of agreement with their caregivers (p<.001). Further, simple slope analyses revealed that high atmospheric pressure during fall was associated with increased engagement This is a provisional file, not the final typeset article (p<.05), while humid and cloudy weather during winter predicted more assent behaviors (p<.001) but also less attentional focusing (p<.05) and interest (p<.01). This study confirms that weather, seasons, and time of day can serve as potential indicators and supplement behavioral observation to elicit the emotional and behavioral states of children with PIMD/IDs. These findings underscore the importance of considering these factors when designing meaningful interactions and communication interventions for this population.